2021
DOI: 10.1177/10980482211010248
|View full text |Cite
|
Sign up to set email alerts
|

AEJMC Advertising Division 2020 Teaching Pre-Conference Review: Embracing Diversity Equity and Inclusion Across the Advertising Curriculum-Learning from the Pros

Abstract: The Advertising Division of the Association for Educators in Journalism and Mass Communication held its 23rd annual Teaching Pre-Conference, virtually, on the topic of diversity, equity, and inclusion in the advertising industry. Six advertising professionals with DEI experience were invited to share their insights. In short, the key findings are that the lack of diversity remains of paramount importance and will take an ongoing, industry-wide commitment to resolve. In support, advertising educators need to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Diversity and inclusion are essential building blocks for the education of future business leaders (Crittenden et al, 2020). The recommendation for advertising educators is to include DEI discussions throughout the advertising curriculum (Spring et al, 2021). We assert that intentional and experiential classroom projects focused on multiculturalism can result in real-world connectivity and marketability.…”
Section: Advertising and Marketing Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversity and inclusion are essential building blocks for the education of future business leaders (Crittenden et al, 2020). The recommendation for advertising educators is to include DEI discussions throughout the advertising curriculum (Spring et al, 2021). We assert that intentional and experiential classroom projects focused on multiculturalism can result in real-world connectivity and marketability.…”
Section: Advertising and Marketing Implicationsmentioning
confidence: 99%
“…In 2020, even as protests unfolded following the murder of George Floyd by a Minneapolis police officer, the Advertising Division of the Association for Educators in Journalism and Mass Communication (AEJMC) discussed ways that advertising educators should embrace diversity, equity, and inclusion (DEI) across the advertising curriculum. The session focused on insights shared by professionals within the advertising industry (Spring et al, 2021) toward achieving DEI within both advertising pedagogy and professional practice. Participants identified several tactics, including advisory councils and listening forums; "brave spaces for honest conversations"; internships and scholarships; partnerships between advertising professionals and academia; focus on a multicultural pipeline; and recognition of diversity gap in mid-level and senior positions.…”
Section: Introductionmentioning
confidence: 99%
“…Interdisciplinary talks with educators and professionals through conferences, workshops, and forums have been resumed in person post-pandemic. The discussions covered a broad spectrum of diversity, including culture, workplace, and work (Spring et al, 2021). Even during the pandemic, the authors observed increasing virtual talks with prominent scholars and professionals made available to students that would be otherwise limited due to financial burdens.…”
Section: Recommendations and Conclusionmentioning
confidence: 99%